Comparison of The Effectiveness of Lavender and Lemon Aromatherapy Toward Reducing Pain Labor During Active Phase of First Stage - Cahaya Indah Lestari; Rizkia Amilia; Evi Diliana Rospia (Jurnal Kebidanan, 2022)
Based on a survey conducted by the City of Mataram in December 2020, there were 15 maternity patients obtained by 9 patients who said that the pain felt like prickling, heat radiated along the waist and lower abdomen, and based on direct observation during the delivery process someone had used lavender aromatherapy to treat pain. overcome pain during childbirth in the city of Mataram so based on these data felt the need to do this research. The purpose is to analyze the relationship of food intake and characteristics pregnant women with incidence of KEK in pregnant women in the town of Mataram city 2020. The type of research used in this study was a quasi-experimental using a non-equivalent control group pretest and posttest research design with the provision that 15 maternity mothers were given lavender aromatherapy and 15 respondents were given lemon aromatherapy. The sampling technique in this study uses total sampling. There was a significant difference before and after being given lavender aromatherapy with p value 0.01 < 0.05, the same result was obtained in the lemon aromatherapy group with p value 0.01 < 0.025. From the posttest results of both groups, it can be concluded that the average decrease in lavender aromatherapy was 0.53 compared to the lemon aromatherapy group, which was 0.3, which means that there was a significant decrease in pain intensity in the lavender aromatherapy group compared to the lemon aromatherapy group. Conclusion there is a Comparison of the Effectiveness of Lavender and Lemon Aromatherapy on Reducing Pain Intensity in Active Phase I Labor.